OUTLINE FOR ISSUES PRESENTATION TO MANAGEMENT COMMITTEE FOR 940330 BREAKFAST BEFORE BOARD MEETING - R,JG (Tufts Archival Research Center, 2007)
Marginalia; Illegible/Difficult to Read; Document outlining issues for the Labor Management Committee (LMC). Cites the anti-tobacco attitude of the government as a severe detriment to the tobacco industry's goals. Lists many of the activities the government has undertaken to discourage tobacco use as well as many of the steps the tobacco industry has taken to combat this.